Método de extracción del concentrado de carambola (averrhoa carambola l.) en el cantón Mocache - Moreira Valencia, Teresa Margarita (2015)
This research was conducted at the Experimental Farm " La María " State Technical University of Quevedo, in the Laboratory of Food Science, Faculty of Animal Science, located at Km 7 1/2 via Quevedo - El Empalme, in the province of Los Ríos. The objectives were: 1) Identify extraction methods concentrate more appropriate carambola as to maintain quality; 2) Select concentrate costs carom benefit. A completely randomized design with five replications was used. Three methods of extraction (liquid, pulping and pressing) were used. Tukey's test was used for comparison between. In the variables pH, Brix and humidity, there were no statistically significant differences between issuing securities in pH 3.86- 4.07, 9.30- 9.36% in ° Brix and moisture from 0.72 to 0.65 % moisture, as corresponds to protein and acidity if presented statistically significant differences with values of 0.65 to 0.72 and 0.52-1.32 acidity protein. With regard to organoleptic analysis concentrates carambola presented; a taste, sweetness and light yellow while in taste and smell carambola was moderate overall appearance also evaluating the tasters found that the best treatment was T2 pulping. The benefit / cost to the best treatment (T2) is issuing a $ 5.34 return on $ 434.39. And a yield of 70.73 % in the preparation of concentrated carom.